2017
DOI: 10.1186/s12916-017-0777-9
|View full text |Cite
|
Sign up to set email alerts
|

What is the association of hypothyroidism with risks of cardiovascular events and mortality? A meta-analysis of 55 cohort studies involving 1,898,314 participants

Abstract: BackgroundWhether hypothyroidism is an independent risk factor for cardiovascular events is still disputed. We aimed to assess the association between hypothyroidism and risks of cardiovascular events and mortality.MethodsWe searched PubMed and Embase from inception to 29 February 2016. Cohort studies were included with no restriction of hypothyroid states. Priori main outcomes were ischemic heart disease (IHD), cardiac mortality, cardiovascular mortality, and all-cause mortality.ResultsFifty-five cohort studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 44 publications
(62 reference statements)
5
58
0
5
Order By: Relevance
“…In a meta‐analysis of 55 cohort studies, hypothyroidism is associated with higher risks of cardiac mortality and all‐cause mortality compared with ET in both the general public and cardiac patients . Recent study demonstrated that hypothyroidism was an independent predictor of cardiovascular and cerebral events in patients who received PCI; moreover, it highlighted that adequate thyroid replacement treatment could prevent cardiovascular events .…”
Section: Discussionmentioning
confidence: 99%
“…In a meta‐analysis of 55 cohort studies, hypothyroidism is associated with higher risks of cardiac mortality and all‐cause mortality compared with ET in both the general public and cardiac patients . Recent study demonstrated that hypothyroidism was an independent predictor of cardiovascular and cerebral events in patients who received PCI; moreover, it highlighted that adequate thyroid replacement treatment could prevent cardiovascular events .…”
Section: Discussionmentioning
confidence: 99%
“…Among the 52 included eligible MAs, 4628–73 (46/52, 88.5%) were published in English, and the rest74–79 (6/52, 11.5%) were published in Chinese. The 52 included MAs contained 685 studies, with an average of 13.2 (range: 3–39) studies per article.…”
Section: Resultsmentioning
confidence: 99%
“…Ten39 40 43 49 57 58 65 68–70 MAs were about the associations between OH and other diseases, and 3528–36 38 42 44–47 50–56 59–64 66 67 75–79 MAs have shown the associations between SCH and other diseases. Seven37 41 48 71–74MAs have investigated the effects of both OH and SCH on other diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Наличие СГ было ассоциировано с инфарктом миокарда в анамнезе и атеросклерозом аорты [8]. По данным метаанализа 55 когортных исследований с включением 1898314 больных было установлено, что СГ (повышенное значение тиреотропного гормона [ТТГ] при нормальном уровне свободного тироксина) повышает риск развития ишемической болезни сердца и смертности по сравнению с пациентами с эутиреоидным статусом [9]. Результаты обследования большой когорты больных ишемической болезнью сердца (ИБС, n=870), поступивших в многопрофильный стационар Санкт-Петербурга для коронарографического исследования, показали, что СГ ассоциирован с многососудистым поражением коронарных артерий и является независимым дополнительным фактором сердечно-сосудистого риска [10].…”
Section: Detectability Of Subclinical Hypothyroidism выявляемость субunclassified